2021
DOI: 10.1038/s41598-021-82201-8
|View full text |Cite
|
Sign up to set email alerts
|

A metabolomic approach to target antimalarial metabolites in the Artemisia annua fungal endophytes

Abstract: Fungal endophytes are a major source of anti-infective agents and other medically relevant compounds. However, their classical blinded-chemical investigation is a challenging process due to their highly complex chemical makeup. Thus, utilizing cheminformatics tools such as metabolomics and computer-aided modelling is of great help deal with such complexity and select the most probable bioactive candidates. In the present study, we have explored the fungal endophytes associated with the well-known antimalarial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Hence, OPLS analysis was performed to extract AGI activity-related variations from those that are orthogonal to the response variable The OPLS model exhibited a cumulative R 2 Y and Q 2 value of 0.61 and 0.546, respectively. The observed R 2 and Q 2 values could be taken as fair indicators of the model's adequacy [73]. Moreover, the root means squared error of estimation (RMSEE) at 16.8 and root mean squared error of cross-validation (RMSEcv) at 18.1 exhibited a good fit and prediction capacity of the OPLS model, respectively.…”
Section: Multivariate Analysismentioning
confidence: 91%
“…Hence, OPLS analysis was performed to extract AGI activity-related variations from those that are orthogonal to the response variable The OPLS model exhibited a cumulative R 2 Y and Q 2 value of 0.61 and 0.546, respectively. The observed R 2 and Q 2 values could be taken as fair indicators of the model's adequacy [73]. Moreover, the root means squared error of estimation (RMSEE) at 16.8 and root mean squared error of cross-validation (RMSEcv) at 18.1 exhibited a good fit and prediction capacity of the OPLS model, respectively.…”
Section: Multivariate Analysismentioning
confidence: 91%
“…What is more, emodin has a therapeutic potential for the treatment of ulcerative colitis [22], keratitis [23], cardiac fibrosis [24] and rheumatoid arthritis [25]. According to the most recent research reports, emodin isolated from Artemisia annua has antimalarial properties [26]. In an in vivo study it was demonstrated that emodin acts as an analgesic [27].…”
Section: Pharmacological Effects Of Emodinmentioning
confidence: 99%
“…Accordingly, we subjected the metabolites (1-25) identified in the P. lamellosa-derived extracts (i.e., CE and EE) to the neural networking-based prediction software PASS. This software has shown very good success rate in its predictions, particularly for predictions higher than Pa = 0.5 [27][28][29][30][31][32][33].…”
Section: Target Prediction and Docking Analysismentioning
confidence: 99%
“…Moreover, they showed a number of hydrophobic interactions with LEU-5, MET-21, HIS-46, TYR-50, and LYS-6 (Figure 6). sPLA2 has been reported to have a crucial role in the growth and development of different types of human cancers (e.g., breast, prostate, liver, and skin), and identified to be a promising target to control these types of tumors [24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Target Prediction and Docking Analysismentioning
confidence: 99%
See 1 more Smart Citation